Deterministic rainfall induced landslide approaches, advantages and limitations. - Omar, Husaini; Kim Huat, Bujang; Md Yusoff, Zainuddin; Safaei, Mehrdad; Ghiasi, Vahed (2011)
There are many approaches to assessing slope stability for landslide susceptibility and hazard mapping that mostly running in GIS platform by define a spatial extension with less error or more successes rate and availability of predictive landslide modeling. These models can be classified into four main methods: inventory, heuristic, statistic and deterministic. Recent studies have shown that the best approaches for landslide spatial prediction is the application of deterministic slope stability models, combined with steady state or transient models for hill slope hydrology. These may provide scenarios of potential instability under changing environmental and climatic conditions but are very data demanding at watershed scales. Several authors have developed GIS models by coupling a dynamic hydrological model that simulates the pore pressure over time with a slope stability model that quantifies the susceptibility as the critical pore pressure threshold. Therefore, those require with simplification of the landslides type and depth. The geotechnical model, which is deterministic or probabilistic, has been widely employed in civil engineering and engineering geology for slope stability analysis. A deterministic approach was traditionally considered sufficient for both homogenous and non-homogenous slopes. Calculating the safety factor requires geometrical data and information on the pore water pressure and ground water table. Base on literature review, there is some lack of a systematic comparison of different techniques in order to outline advantages and limitations of the methods to model the spatial distribution of landslides. We can use deterministic approaches for rainfall, and earthquake induced landslide or landslide run out modeling.